Time course effect of blood flow restriction strength training and detraining on haemodynamics, strength, and muscle thickness - Brandner, C.; Kidgell, D.; Warmington, S. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Blood flow restriction (BFR) in combination with light-load strength training (LST) provides gains in strength and muscle mass similar to traditional heavy-load strength training (HST). However, haemodynamic adaptations to BFR training are less well understood. While in addition, there is a lack of data that directly compares training responses between BFR, HST, and LST. Therefore, the purpose of this study was to examine the time course effect of combined lower- and upper-body BFR training on haemodynamics, and muscle strength and size, in comparison with both HST and LST. Methods: Untrained participants (n=19 [14M, 5F]; 23 ± 0.5 yrs, 172.5 ± 2.2 cm, 68.4 ± 2.5 kg) were randomized into training groups. Either, HST (n=7; 70% 1RM), LST (n=7; 20% 1RM), or BFR (n=5; 20% 1RM with restriction pressure set at 60% total limb occlusion pressure). Training (3d/wk) comprised sets of knee extension (KE), squat (SQ), calf raise (CR), bench press (BP), seated row (SR), and bicep curl (BC) exercises. Outcome measures were taken at week 0, mid point (wk 4), end of training (wk 8), and after four weeks detraining (wk 12). Dual-energy X-ray absorptiometry (DXA) was used to measure whole body, arm, and leg muscle mass, while ultrasound was used to measure muscle thickness (MTH) at 7 sites. Heart rate (HR), blood pressure, cardiac output (Q), and stroke volume (SV) responses to KE exercise were taken at baseline, and during the final set of the exercise bout at each testing week. Results: KE, SQ, and CR strength increased in both BFR and HST at wk 4 (range 8-20%) and wk 8 (range 9-28%) compared with baseline, while BP, SR, and BC strength increased only in HST (range 5-15%). DXA data were not different between groups. MTH increased in both BFR and HST for biceps brachii (range 5-10%), but additionally quadriceps (4 and 10%) and hamstrings (2 and 9%) in HST only. Baseline haemodynamic parameters were similar between groups at all measurement weeks, with training adaptations only evident during exercise for BFR and HST whereby systolic blood pressure was lower at wk 4 and wk 8 compared with wk 0. Discussion: Previous BFR training interventions have typically only used single joint exercises in isolation. Therefore, a novel aspect of this study was that both upper- and lower-body training was performed. This study provides further evidence that BFR training increases muscle strength and size similar to HST, with some beneficial reductions in exercising haemodynamic stress responses over time. These data support the potential for BFR to be prescribed to clinical populations that have limited strength training capacity such as the elderly or due to muscle atrophy or weakness following injury. However, future studies should examine haemodynamic responses in populations with compromised cardiovascular health before BFR be recommended.